Pengaruh Edukasi Gizi Leaflet Kementerian Kesehatan pada Pengetahuan Pola Konsumsi Balita di Desa Rantoe Panyang Timur - Permas, Ria; Iskandar, Wardah (Polyscopia, 2024)
Toddler nutrition is critical for children aged 1-5 years to support optimal growth and development, requiring a balanced diet rich in protein, carbohydrates, healthy fats, vitamins, and minerals. This study aims to evaluate the influence of nutrition education delivered through leaflets on enhancing parental knowledge about proper nutrition for toddlers. Conducted in Rantoe Panyang Village, this research employed a quasi-experimental design with a pre-test and post-test control group. The population consisted of 62 mothers with toddlers, selected using total sampling to include the entire population. The findings revealed a significant relationship between nutrition education using leaflets and improved parental knowledge. The study concludes that nutrition education facilitated through leaflet media positively impacts parental understanding of toddler nutrition. These results underscore the importance of targeted educational interventions in improving knowledge and dietary practices among parents, ultimately contributing to better nutritional outcomes for children.